2020
DOI: 10.32604/cmes.2020.011920
|View full text |Cite
|
Sign up to set email alerts
|

An Classification–Detection Approach of COVID-19 Based on Chest X-ray and CT by Using Keras Pre-Trained Deep Learning Models

Abstract: The Coronavirus Disease 2019 (COVID-19) is wreaking havoc around the world, bring out that the enormous pressure on national health and medical staff systems. One of the most effective and critical steps in the fight against COVID-19, is to examine the patient's lungs based on the Chest X-ray and CT generated by radiation imaging. In this paper, five keras-related deep learning models: ResNet50, InceptionResNetV2, Xception, transfer learning and pre-trained VGGNet16 is applied to formulate an classification-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 22 publications
0
23
0
2
Order By: Relevance
“…Early diagnosis of COVID-19 is important to minimize human-to-human transmission and patient care. Recently, the separation and quarantine of healthy people from the infected or persons who suspect that they are carrying the virus is the most effective technique to avoid the spread of COVID-19 (Deng 2020). Machine-learning techniques role showed an important understandings of the COVID-19 diagnosis, such as lung computed tomography (CT) scan whether it can be regarded as the first screening or an alternative test for the real-time inverse transcriptase-polymerase chain reaction (RT-PCR), and the differences between COVID-19 pneumonia and other viral pneumonia using CT scan of the lungs (Kassani et al (2004)).…”
Section: Covid-19mentioning
confidence: 99%
“…Early diagnosis of COVID-19 is important to minimize human-to-human transmission and patient care. Recently, the separation and quarantine of healthy people from the infected or persons who suspect that they are carrying the virus is the most effective technique to avoid the spread of COVID-19 (Deng 2020). Machine-learning techniques role showed an important understandings of the COVID-19 diagnosis, such as lung computed tomography (CT) scan whether it can be regarded as the first screening or an alternative test for the real-time inverse transcriptase-polymerase chain reaction (RT-PCR), and the differences between COVID-19 pneumonia and other viral pneumonia using CT scan of the lungs (Kassani et al (2004)).…”
Section: Covid-19mentioning
confidence: 99%
“…They reported that using the VGG16 technique gave the highest classification accuracy of 80% among the other four proposed models. The same procedure has been followed in [ 35 , 54 ]. The authors in [ 54 ] used five pre-trained models, including ResNet50, InceptionResNetV2, and Xception.…”
Section: The Study Taxonomymentioning
confidence: 99%
“…Deng, et.al. [7] menggunakan pre-trained model Keras pada data Chest X-ray dan Chest CT. Akurasi yang dihasilkan dikedua dataset tersebut adalah 84% dan 75%. Performa yang dihasilkan tersebut masih memiliki akurasi di bawah 90%.…”
Section: Pendahuluanunclassified
“…Dataset citra Chest X-ray yang digunakan pada kasus ini memiliki jumlah yang berbeda tiap kelas klasifikasinya seperti yang ada pada Tabel 1. Rumus perhitungan weighted metric dapat dilihat pada Persamaan (7).…”
Section: = +unclassified